KEBIJAKAN PENERTIBAN HEWAN TERNAK DI WILAYAH DESA PASALAE KECAMATAN GENTUMA RAYA KABUPATEN GORONTALO UTARA - Razak, Darmawaty Abd; Nusi, Marten; Prahara, Sandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to examine the implementation of Village Regulation Number 01 of 2021 concerning Animal Control in Pasalae Village, Gentuma Raya District, North Gorontalo Regency. The background of this research is based on the ongoing problems related to freely roaming livestock, which potentially disrupt public order, safety, and community comfort. This study employs a qualitative research approach, with data collected through interviews, observations, and documentation. A total of eight informants participated in this study, consisting of village government officials, policy implementers, and community members. The results of the study indicate that the implementation of Village Regulation Number 01 of 2021 has not been carried out optimally. In terms of communication, the process of information dissemination and coordination among implementing actors conducted by the village government remains limited, resulting in uneven public understanding of the village regulation. From the perspective of resources, the village government faces limitations in human resources, particularly technical personnel responsible for animal control and public socialization activities. Regarding the disposition or attitude of implementers, although there is a commitment between policy makers and implementers, its realization in the field is still not optimal. Furthermore, from the bureaucratic structure perspective, the Standard Operating Procedures (SOPs) owned by the village government have not been adequately socialized to the community. Consequently, the community does not fully understand the procedures and provisions stipulated in the village regulation. Therefore, improvements in communication, strengthening of human resources, and continuous socialization of SOPs are necessary to enhance the effectiveness of the implementation of the village regulation on animal control.